Students of the Medical College against the background of three other faculties of the Jan Kochanowski University in Kielce - Mlodawski, Jakub; Swiercz, Anna; Mlodawska, Marta; Piąta, Aleksandra; Gawdzik, Barbara; Swiercz, Grzegorz (Journal of Education, Health and Sport, 2023)
The need to limit people-to-people contacts during the COVID-19 pandemic introduced the need for distance learning at universities. After two years of pandemic restrictions, we decided to check the opinion of medical students and three other faculties on the conducted classes and compare groups with each other. We conducted a survey research based on standardized questionnaire which included 306 students from four faculties of the Jan Kochanowski University in Kielce – Faculty of Law and Social Sciences (1), Medical College (2), Faculty of Exact and Life Sciences (3), Faculty of Pedagogy and Psychology (4). Students did not differ in the assessment of most types of classes conducted in a virtual form. The exceptions were virtual meetings in a group of students, which were better assessed at the faculty no. 1 compared to 2 and 4. Students of Medical College faculty differed in terms of assessing level of distance learning and their own involvement. Their ratings on these two issues were the lowest among the four groups. The students of individual faculties did not differ in terms of assessing the effectiveness of the elements of education in the traditional and remote modes of operation. The subjective assessment of distance learning by students from various faculties shows subtle differences. The transition to distance education resulted in a decline in the involvement of medical students in their education and a subjective decrease in quality of teaching comparing to other faculties. This opinion may be taken into account when adapting curricula and selecting the type of classes to be conducted in the course of distance or hybrid learning.